Initiatives supporting breastfeeding - Chrásková, Jana; Boledovičová, Mária (Jihočeská univerzita v Českých Budějovicích, Zdravotně sociální fakulta, 2016)
The paper focuses on mapping the principal field supporting the process of breastfeeding and lactation. It brings extensive scientifically well-founded benefits of breastfeeding for healthy growth and development of a child, including activities which are concerned with the support of breastfeeding within the international scale. It presents basic documents which declare the right to breastfeeding and lays stress on the activity of the international network – IBFAN (International Baby Food Action Network), which intervenes in the sphere using optimal nutrition methods. One part also deals with the historical survey of the initiative – Baby-Friendly Hospital (BFHI) within the international scale, with the implementation of the initiative BFHI into the socio-cultural environment of the Czech Republic, where an irreplaceable institution is the National Lactation Centre in The Faculty Thomayer Hospital in Prague-Krč (FTN). It focuses on the description of a situation when there is a recommended procedure of breastfeeding of a full-term newborn including the WHO recommendation, but despite of this, in the Czech Republic, full-term newborns are supplementary fed without any indicators. Stated at the end are the articles concerning the promotion of breastfeeding which are publicized in the programme Health 2020 – The National Strategy of Protection and Support of Health and Illness Prevention, whereas the area of interest is health and well-being of citizens of the European region of the World Health Organization and which was already supported by the government of the Czech Republic in 2014.
Keywords: Baby-Friendly Hospital Initiative; International Baby Food Action Network; breastfeeding; support of breast feeding; Health 2020